ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI PENDAPATAN KOPI KELILING STUDI KASUS DI KECAMATAN RAPPOCINI KOTA MAKASSAR - Tiara, Safira Almey; Suarni, Agusdiwana; Nurlina, Nurlina (Jurnal Ekonomi Sakti, 2025)
This study analyzes the factors influencing the income of mobile coffee vendors in Rappocini District, Makassar. The study focuses on three main variables: business capital, working hours, and education level. Using a quantitative approach and survey method, data were collected from vendors selected using the Slovin formula. Data analysis was performed using multiple linear regression and classical assumption tests using SPSS IBM Statistics 26. The results indicate that all three independent variables have a positive and significant effect on income. Specifically, business capital showed a t-value of 5.147 (significance 0.002), working hours 4.177 (significance 0.001), and education level 5.302 (significance 0.03). These findings underscore the importance of capital management, efficient work time allocation, and educational background in increasing the efficiency and income of mobile coffee vendors. Therefore, this study contributes to the literature on informal sector entrepreneurship and can serve as a reference for scholars, business actors, and policymakers in designing strategies for empowering micro-enterprises in urban areas. Keywords: Business Capital, Working Hours, Education Level, Income, Mobile Coffee